A educação patrimonial no Arquivo Histórico Municipal de Santa Maria: um olhar direcionado aos multiplicadores de ações nas escolas - Calil, Daniéle Xavier (2011)
The present work was developed during the Masters Course in the Vocational Graduation Program in Cultural Heritage at the Federal University of Santa. This research aimed at investigating the reality of the Heritage Education in the Elementary School system in Santa Maria/RS to, after knowing this reality, propose subsides of guidelines focusing educator so that they can bring children and teenagers closer to the local heritage, especially the documental heritage in custody of the Municipal Historical Archive. The dialogue between Archive and School is critical to make students understand the importance to preserve their local heritage which is their own heritage. Starting from this and, considering the fact that the Municipal Historical Archive is visited by just a few students from elementary school, we tried to investigate the causes of this detachment. Our study is a descriptive field research with a quantitative and qualitative approach. To investigate the Heritage Education scenario in the city of Santa Maria we used a questionnaire that was sent to fifty-eight private, State and Municipal schools of the administrative urban center region and its neighboring regions but only twenty-one schools returned with some feedback. With the analysis of the collected data we can infer that the Heritage Education is present at school but is not worked from the Municipal Historical Archive documental heap because the educators do not know the services and research possibilities offered by the information unit. In this way, as educators are actions multipliers at school, the Heritage Education Program from the Santa Maria Municipal Historical Archive began with actions directe to the educators, such as the Meeting and the Orientation Guide for Educators.